Yann Le Meur #SportScienceInfographics - Ross, A. (British Journal of Sports Medicine, 2018)
Few can say they have genuinely influenced how their industry communicates, but Yann can safely make such statements. His modesty makes him the first to admit he adapted the idea, but credit to him for the wonderful job he has done on devoting himself to the production of those crazy little infographics. They are ubiquitous in our industry and have permeated through the sports science fraternity to be a brilliant information dissemination tool. (François Bieuzen; Philippe Kuentz; Rob Duffield)